Predictors of Colorectal Cancer Screening in Two Underserved U.S. Populations: A Parallel Analysis - Bernardo, Brittany M.; Gross, Amy L.; Young, Gregory; Baltic, Ryan; Reisinger, Sarah; Blot, William J.; Paskett, Electra Diane (Frontiers in Oncology, 2018)
Background Despite declining colorectal cancer (CRC) incidence and mortality rates in the U.S., significant geographic and racial disparities in CRC death rates remain. Differences in guideline-concordant CRC screening rates may explain some of these disparities. We aim to assess individual and neighborhood-level predictors of guideline-concordant CRC screening within two cohorts of individuals located within CRC mortality geographic hotspot regions in the U.S. Methods A total of 36,901 participants from the Southern Community Cohort Study and 4,491 participants from the Ohio Appalachia CRC screening study were included in this study. Self-reported date of last CRC screening was used to determine if the participant was within guidelines for screening. Logistic regression models were utilized to determine the association of individual-level predictors, neighborhood deprivation, and residence in hotspot regions on the odds of being within guidelines for CRC screening. Results Lower household income, lack of health insurance, and being a smoker were each associated with lower odds of being within guidelines for CRC screening in both cohorts. Area-level associations were less evident, although up to 15% lower guideline adherence was associated with residence in neighborhoods of greater deprivation and in the Lower Mississippi Delta, one of the identified CRC mortality hotspots. Conclusion These results reveal the adverse effects of lower area-level and individual socioeconomic status on adherence to CRC guideline screening.